2021
DOI: 10.3390/genes12101624
|View full text |Cite
|
Sign up to set email alerts
|

WDR36-Associated Neurodegeneration: A Case Report Highlights Possible Mechanisms of Normal Tension Glaucoma

Abstract: WDR36 is one of a number of genes implicated in the pathogenesis of adult-onset primary open angle glaucoma (POAG). Here we describe in detail the phenotype of a patient with pathogenic variation in WDR36 who presented with a protracted history of central vision loss. On exam visual acuities were at 20/100 level, had a tritan color defect and showed central arcuate visual field defects on visual field testing. Enlarged cup-to-disk ratios with normal intraocular pressures were associated with severe thinning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Monemi et al demonstrated WDR36 gene expression in the lens, iris, ciliary muscles, ciliary body, trabecular meshwork, retina, and optic nerve by RT-PCR with four pathogenic variants (p.N355S, p.A449T, p.R529Q and p.D658G) associated with adult-onset POAG with implications for both high-and low-pressure glaucoma [64]. In our study, we detected the variant p.E298N in the WDR36 gene in a patient with severe LTG, whose phenotype was very similar to another reported LTG patient with a variant (p.N355S) in the WDR36 gene [58]. Some of the patients carrying rare variants (patient 1 and patient 8) presented with thin pachymetry, which is a known endophenotypic trait that increases the degree of severity of the glaucoma cases, whether this trait has been directly linked to the variant described or is a consequence of other genetic/epigenetic influences still has to be elucidated.…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…Monemi et al demonstrated WDR36 gene expression in the lens, iris, ciliary muscles, ciliary body, trabecular meshwork, retina, and optic nerve by RT-PCR with four pathogenic variants (p.N355S, p.A449T, p.R529Q and p.D658G) associated with adult-onset POAG with implications for both high-and low-pressure glaucoma [64]. In our study, we detected the variant p.E298N in the WDR36 gene in a patient with severe LTG, whose phenotype was very similar to another reported LTG patient with a variant (p.N355S) in the WDR36 gene [58]. Some of the patients carrying rare variants (patient 1 and patient 8) presented with thin pachymetry, which is a known endophenotypic trait that increases the degree of severity of the glaucoma cases, whether this trait has been directly linked to the variant described or is a consequence of other genetic/epigenetic influences still has to be elucidated.…”
Section: Plos Onesupporting
confidence: 85%
“…Similarly, contradictory results are reported for the association of pathogenic variants in the WDR36 gene with glaucoma. Whereas several studies have indicated that genetic variants in WDR36 gene are contributing risk factors for glaucoma progression and severity [54][55][56][57][58], recent clinical trials and meta-analyses have suggested a lack of effect [59][60][61]. However, it is known that this gene has a connection to glaucoma susceptibility and even to retinal homeostasis [62,63].…”
Section: Plos Onementioning
confidence: 99%
“…WDR36 is expressed in a variety of tissues, including the ciliary body, iris, lens, optic nerve, retina, sclera, and trabecular meshwork. [ 119 ] In 2005, WDR36 was linked to POAG pathogenesis. In that study, four variations were identified in the WDR36 gene (c.1064A > G; c.1345G > A; c.1586G > A; c.1973A > G), and these variations covered approximately 6% of the POAG patients.…”
Section: Wd Repeat Domain 36mentioning
confidence: 99%